Valutare, progettare, implementare. I percorsi punitivo-rieducativi del sistema penale minorile tra giustizia riparativa e terzo settore - Fabio Ricciardi (Archivio Antropologico Mediterraneo)
This contribution intends to try to introduce possible interpretations or future research regarding the criminal expiation paths imposed by the Judicial Authority on juvenile offenders observed through the lens of ethnography. In a context where the various institutions are flanked by individuals of a private nature (third sector entities) and re-education professionals (social workers, mediators, educators, psychologists), the result of the atonement and re-education path identified is the result of mediation between the various actors and the knowledge they put in place. Hence the proliferation of re-educational (stay in the community, probation for social service, criminal mediation). These tools, designed with the aim of combining the punitive aspect with that of subjective repentance, try to carry on the implementation of personal skills, remaining in the balance between the need to guarantee the expiation of the sentence and that of producing new subjectivities, able to free themselves from conditions of social marginality as long as the characteristics suitable for inclusion in the productive system are acquired.